From Girl to Workshop Facilitator (2009)
“In 2005, I was a student and, from day one at EAFIT Children's University, I stuck to the green shirt. I was fortunate to stay here as a workshop facilitator, that helped me to train myself and learn from others, taking from them those elements that made them true masters. It is beautiful to see how joyful learning is made here. It is nice to see how knowledge arises through the sensitive sphere”.